Three new species of Dikrella Oman (Hemiptera: Cicadellidae) associated to urban trees in Argentina - Pereyra, Mora; Hamity, Veronica C.; Albarracín, Erica Luft; Catalano, Ines; Paradell, Susana (Zootaxa, 2025)
Three new species of Dikrella (Readionia) Oman, D. lilloi sp. nov., D. urbana sp. nov. and D. yungaensis sp. nov. from Tucumán and Jujuy provinces, Argentina, are described. Detailed morphological descriptions with genitalia illustrations of the new species and a key for identification of males of Dikrella (Readionia) are provided.